PENGARUH MODEL PEMBELAJARAN INTERAKTIF TERHADAP MINAT BELAJAR SISWA PADA MATA PELAJARAN IPAS MATERI INDONESIAKU KAYA BUDAYA PADA SISWA KELAS IV DI SD NEGERI 101805 BATU REJO: Quaisy Eksperimental - Cahyani, Apria; Shabrina Anshor, Arrini; Rapita Silalahi, Beta; Napitupulu, Safrida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The background of this research is based on the fact that students' interest in learning in the Natural and Social Sciences (IPAS) subject, especially in the material "My Indonesia is Rich in Culture," is still relatively low, which is indicated by the lack of active participation, enthusiasm in learning, and learning outcomes have not reached the minimum completion criteria (KKM) or learning outcomes are still relatively low. The interactive learning model was created to create a more interesting, active, and collaborative learning atmosphere so that it is expected to increase student involvement in the learning process. This research uses a quantitative approach with a quasi-experimental method and a Nonequivalent control group design. The research subjects were 40 fourth-grade students divided into two groups, namely class IVA as an experimental class using an interactive learning model and class IVB as a control class using a conventional learning model. Data were collected through observation and questionnaires on students' learning interests before and after treatment (pretest and posttest). Data analysis was conducted using normality test, homogeneity test, and t-test with the help of SPSS version 25 program. The results showed that there was a significant difference between the pretest and posttest results in the experimental class compared to the control class. The average value of students' learning interest in the experimental class increased significantly after the interactive learning model was implemented. Thus, it can be concluded that the interactive learning model has a positive and significant effect on increasing students' learning interest in the Natural Sciences subject with the material My Indonesia is Rich in Culture.